Add‐on cannabidiol in patients with Dravet syndrome: Results of a long‐term open‐label extension trial - Scheffer, Ingrid E.; Halford, Jonathan J.; Miller, Ian; Nabbout, Rima; Sanchez‐Carpintero, Rocio; Shiloh‐Malawsky, Yael; Wong, Matthew; Zolnowska, Marta; Checketts, Daniel; Dunayevich, Eduardo; Devinsky, Orrin (Epilepsia (Copenhagen), 2021)
Objective Add‐on cannabidiol (CBD) reduced seizures associated with Dravet syndrome (DS) in two randomized, double‐blind, placebo‐controlled trials: GWPCARE1 Part B (NCT02091375) and GWPCARE2 (NCT02224703). Patients who completed GWPCARE1 Part A (NCT02091206) or Part B, or GWPCARE2, were enrolled in a long‐term open‐label extension trial, GWPCARE5 (NCT02224573). We present an interim analysis of the safety, efficacy, and patient‐reported outcomes from GWPCARE5. Methods Patients received a pharmaceutical formulation of highly purified CBD in oral solution (100 mg/ml), titrated from 2.5 to 20 mg/kg/day over a 2‐week period, added to their existing medications. Based on response and tolerance, CBD could be reduced or increased to 30 mg/kg/day. Results Of the 330 patients who completed the original randomized trials, 315 (95%) enrolled in this open‐label extension. Median treatment duration was 444 days (range = 18–1535), with a mean modal dose of 22 mg/kg/day; patients received a median of three concomitant antiseizure medications. Adverse events (AEs) occurred in 97% patients (mild, 23%; moderate, 50%; severe, 25%). Commonly reported AEs were diarrhea (43%), pyrexia (39%), decreased appetite (31%), and somnolence (28%). Twenty‐eight (9%) patients discontinued due to AEs. Sixty‐nine (22%) patients had liver transaminase elevations >3 × upper limit of normal; 84% were on concomitant valproic acid. In patients from GWPCARE1 Part B and GWPCARE2, the median reduction from baseline in monthly seizure frequency assessed in 12‐week periods up to Week 156 was 45%–74% for convulsive seizures and 49%–84% for total seizures. Across all visit windows, ≥83% patients/caregivers completing a Subject/Caregiver Global Impression of Change scale reported improvement in overall condition. Significance We show that long‐term CBD treatment had an acceptable safety profile and led to sustained, clinically meaningful reductions in seizure frequency in patients with treatment‐resistant DS.